Restless legs syndrome and impact on work performance - Samara, Diana (Universa Medicina, 2009)
Restless legs syndrome (RLS) is a neurological sensorimotor disorder characterized by unpleasant sensations in the legs and an uncontrollable urge to move them for relief. The RSL prevalence in the general population is 0.1% - 11.5%, and increases with age, with the highest effect of producing a primary sleep disorder (70%-80%). Women appear to be at increased risk, as do individuals with certain chronic conditions, including renal failure and anemia. The pathophysiology of RLS is incompletely understood, but it probably results from derangements in dopamine and iron metabolism, and has a genetic component. RSL could be idiopathic or secondary (usually related with iron deficiency, terminal renal failure, pregnancy, and spinal cord lesions). RLS patients usually have sleep disorders, so the disease can cause difficulties and problems in occupational and social life. Subjects with RLS symptoms appear to experience significantly more daytime problems, including being late for work, making errors at work, or missing work because of sleepiness. The diagnosis of RLS is made by following the criteria of the International Restless Legs Syndrome Study Group (IRLSSG). Pharmacologic RLS therapy, in which dopaminergic drugs constitute the first line, is effective and may have a dramatic effect on symptoms and quality of life. Identifying and treating RLS may improve sleep quality, daytime function and work performance.